A Comprehensive Outlook of Synthetic Strategies and Applications of Redox‐Responsive Nanogels in Drug Delivery - Kumar, Parveen; Liu, Bo; Behl, Gautam (Macromolecular bioscience, 2019)
Increasing recognition of the role of oxidative stress in the pathogenesis of many clinical conditions and the existence of defined redox potential in healthy tissues has led to extensive research in the development of redox‐responsive materials for biomedical applications. Especially, considerable growth has been seen in the fabrication of polymeric nanogel–based drug delivery carriers utilizing redox‐responsive cross‐linkers bearing a variety of functional groups via various synthetic strategies. Redox‐responsive polymeric nanogels provide an advantage of facile chemical modification post synthesis and exhibit a remarkable response to biological redox stimuli. Due to the interdisciplinary nature of the subject, a more profound combined conceptual knowledge from a chemical and biological point of view is imperative for the rational design of redox‐responsive nanogels. The present review provides an insight into the design and fabrication of redox‐responsive nanogels with particular emphasis on synthetic strategies utilized for the development of redox‐responsive cross‐linkers, polymerization techniques being followed for nanogel development and biomedical applications. Cooperative effect of redox trigger with other stimuli such as pH and temperature in the evolution of dual and triple stimuli‐responsive nanogels is also discussed. Redox‐responsive nanogels provide enormous potential in the field of therapeutic delivery, diagnosis, and biomedical applications. This review summarizes various characteristics of nanogels with particular emphasis on synthetic strategies and polymerization methods. Multifunctional redox‐responsive nanogels releasing therapeutics in response to other biological stimuli, that is, temperature and pH and other emerging redox‐active materials are also highlighted.